The numerical analysis of integrated photonics structures for optical beam deflection application - Struk, Przemysław (Photonics Letters of Poland, 2024)
The paper presents a concept and numerical analysis of a fast scanner based on integrated photonics structures including a planar waveguide with a grating coupler combined with a swept source laser as a light source. Full Text: PDF References L. Thylén et al.,"Integrated photonics in the 21st century", Photon. Res. 2 (2014). CrossRef P. Cheben et al., "Subwavelength integrated photonics", Nature 560, (2018). CrossRef D. Zhu et al., "Integrated photonics on thin-film lithium niobate", Adv. Opt. Photonics 13, 2 (2021). CrossRef S Ura et al., "Design of resonance grating coupler", Opt. Express 16, 16 (2008). CrossRef A. Ymeti et al. "Realization of a multichannel integrated Young interferometer chemical sensor", Appl. Opt. 42, 28 (2003). CrossRef E. Auguściuk et al., "Investigation of parameters of the multimode four-layer waveguide structures and their influence on the light propagation", Phot. Lett. Poland 15(3) (2023). CrossRef K. Ezgi et al.,"Technological challenges in the development of silica-titania platform for integrated optics", Phot. Lett. Poland 1, 3 (2009). CrossRef A. Y. Alibhai, "Swept Source Optical Coherence Tomography: a Review", Curr. Ophthalmol. Rep. 6 (2018). CrossRef Y. Chen, Atlas of Swept Source OCT and OCT angiography (Springer 2023). CrossRef P. Struk et.al, "Swept-source optical coherence tomography microsystem with an integrated Mirau interferometer and electrothermal micro-scanner", Opt. Lett. 43, 19, (2018). CrossRef P. Struk, "Design of an Integrated Optics Sensor Structure Based on Diamond Waveguide for Hemoglobin Property Detection", Materials 12, 175 (2019). CrossRef W. Lukosz, "Integrated optical chemical and direct biochemical sensors", Sens. Actuators B Chem 29 (1995). CrossRef P.V. Lambeck, "Integrated optical sensors for the chemical domain", Meas. Sci. Technol. 17, 8 R93 (2006). CrossRef P. Struk, "Numerical analysis of integrated photonics structures for hemoglobin sensor application", Phot. Lett. Poland 12, 2 (2020). CrossRef Exalos ESS-840 datasheet. DirectLink Refractiveindex Database CrossRef